Technological innovation in Small and Medium Enterprises: A bibliometric analysis - Budianto, Roni; Praptapa, Agung; Herwiyanti, Eliada; Puji, Puji; Suyono, Eko; Rusmana, Oman (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: This study aims to determine the development of Small and Medium-sized Enterprises (SMEs) in the digital era. Research Methodology:  The authors used the Scopus database and searched for articles containing keywords such as "technology innovation" AND smes OR "small and medium enterprises." The data were obtained from 1990 to 2023, with a total of 408 documents consisting of 295 articles, 20 book chapters, 67 conference papers, eight conference reviews, one erratum, one note, five retracted documents, and 11 review documents. Results: The study found that the development of publications on technological innovation in SMEs fluctuated but tended to increase. The most productive source and the most impactful author were Institute of Electrical and Electronics Engineers (IEEE) Transactions on Engineering and Management, and most publications were conducted in collaboration with fellow authors from the same country. The most cited country was the United Kingdom, followed by Singapore and the United States of America. The most common topic in publications was technological innovation. Conclusions: This study shows an increasing trend in research on technological innovation in SMEs, highlighting its importance and the role of key sources, authors and countries in shaping the field. Limitations: The study is limited to Scopus-indexed and English-language publications, and the bibliometric approach focuses on trends rather than an in-depth contextual analysis. Contributions: This study highlights the importance of technological innovation in SMEs and its economic impact.